2011
DOI: 10.1158/1541-7786.mcr-10-0472
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Stimulates Preneoplastic Cellular Proliferation Through Activation of the MAPK Pathway

Abstract: Alterations in the microenvironment collaborate with cell autonomous mutations during the transformation process. Indeed, cancer- associated fibroblasts (CAF) and senescent fibroblasts stimulate tumorigenesis in xenograft models. Because senescent fibroblasts accumulate with age, these findings suggest that they contribute to age-related increases in tumorigenesis. Previously we demonstrated that senescent-associated stromal derived osteopontin (OPN) contributes to preneoplastic cell growth in vitro and in xen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 72 publications
3
33
0
Order By: Relevance
“…Osteopontin-triggered signal transduction via integrins or CD44 is primarily related to the evasion, migration, and proliferation of tumor cells (26,41). We observed upregulated CD44 on LK cells in TBM, which then triggered the osteopontin-mediated proliferation of this cell population (Fig.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Osteopontin-triggered signal transduction via integrins or CD44 is primarily related to the evasion, migration, and proliferation of tumor cells (26,41). We observed upregulated CD44 on LK cells in TBM, which then triggered the osteopontin-mediated proliferation of this cell population (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…2A and B, we observed that the levels of CD26, CXCL1, CCL2, and osteopontin were higher in the spleen of TBM compared with na€ ve mice. Among these factors, osteopontin has been shown to promote the growth and progression of certain solid tumors (23)(24)(25)(26)(27)(28), and is known as a key component of the hematopoietic niche in bone marrow (29,30). However, the role of osteopontin in extramedullary myelopoiesis remains poorly understood.…”
Section: Osteopontin Is Increased In Tbmmentioning
confidence: 99%
“…In the present study, we have demonstrated for the first time that the most fundamental function of PDPN in oral SCC cells is mediating cell adhesion through the crosstalk between CD44 and hyaluronic acid, although its functions had been mainly correlated to cell proliferation 30,31 and migration 32,33 in the literature. The PDPN contribution to cell proliferation has now been shown to be a secondary event to cell adhesion, and the present PDPN inhibition by siRNA did not affect cell migration, as shown in either scratch-wound or transwell migration assays.…”
Section: Discussionmentioning
confidence: 77%
“…NF-κB signalling is the major signalling pathway stimulating the induction of some of the major components of SASP, partially via the induction of a DNA damage response that activates NF-κB [92][93][94]. The matricellular protein OPN, known to have a role in tumour progression and metastasis, was also found to be secreted by senescent fibroblasts in skin and to promote preneoplastic keratinocyte cellular proliferation and cell survival through activation of the MAPK pathway [95].…”
Section: The Senescence-associated Secretory Phenotype Of Cafs Promotmentioning
confidence: 99%